The Internalization of Islamic Values in Guiding Students’ Morality Through The Subjects of Aqeeda Akhlaq at Madrasah Aliyah Al Ikhsan Jombang - Naily Rahma (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2017)
Keywords: Islamic Values, Morals guidance, Internalization The formulation of the problem in this research are, firstly, how is the implementation of internalization of Islamic values in guiding students morality through the subjects Aqeeda Akhlaq at Madrasah Aliyah Al Ikhsan Jombang? Second, what are the supporting and inhibiting factors of the internalization of Islamic values in guiding students’ morality through the subjects Aqeeda Akhlaq at Madrasah Aliyah Al Ikhsan Jombang? Third, how is the efforts made by teachers in Madrasah Aliyah Al Ikhsan Jombang in overcoming the obstacles of the internalization of Islamic values in guiding students morality through the subject of Aqeeda Akhlaq?Qualitative approach is used in this research. Data are collected through observation, interview and documentation. The data is analyzed using descriptive analysis which described